The economic impact of the global crises of the 21st century in Hungary - Káposzta, József; Pongrácz, Zsófia; Daróczi, Miklós (Studia Mundi – Economica, 2023)
Economic crises are inherent to a capitalist market economy, so the circumstances of their occurrence are usually close to identical. Some countries’ economies sometimes go into recession, when, in contrast to the business cycle, GDP falls as national economic performance declines. Recessions are influenced by a number of factors, such as the labour market, employment, borrowing rates and other monetary policy instruments. In our study, we look for correlations between the effects of the global recessions we have analysed, as their effects have all affected incomes, employment and inflation. The impact of the crises is to worsen industrial performance, reduce the value of investment and, in conjunction with this, the level of consumption. It can be concluded that economic crises are inherent to the capitalist market economy, and that the conditions under which they occur are therefore usually almost identical, so that an analysis of their interrelationships and their interdependence can help to mitigate the negative effects of recurrent economic crises. In our study, we examined the relationship between the global financial crisis of 2008 and the economic recession caused by Covid-19 in 2019 and looked for the interconnections between their effects.